2022
DOI: 10.2147/idr.s377411
|View full text |Cite
|
Sign up to set email alerts
|

A Prognostic Model for In-Hospital Mortality in Critically Ill Patients with Pneumonia

Abstract: Purpose To determine the utility of a novel serum biomarker for the outcome prediction of critically ill patients with pneumonia. Patients and Methods A retrospective analysis of critically ill patients was performed at an emergency department. The expression and prediction value of parameters were assessed. Binary logistic regression analysis was utilized to determine the indicators associated with in-hospital mortality of pneumonia patients. The Last Absolute Shrinkag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Characterized by raised BUN concentration, AKI was independently associated with the short-term mortality of CAP patients ( 30 , 31 ). Earlier studies indicated that individuals who did not survive CAP had elevated BUN levels ( 32 , 33 ). Consistent with previous studies on SCAP, this investigation revealed that the BUN level remained a significant predictive indicator of mortality, as demonstrated by multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Characterized by raised BUN concentration, AKI was independently associated with the short-term mortality of CAP patients ( 30 , 31 ). Earlier studies indicated that individuals who did not survive CAP had elevated BUN levels ( 32 , 33 ). Consistent with previous studies on SCAP, this investigation revealed that the BUN level remained a significant predictive indicator of mortality, as demonstrated by multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies on the prognosis of SCAP, either the study population was outside the ICU[8-10], the risk factors for mortality were not readily available clinically [9,10], no relevant predictive model was developed [11], or the model developed was not externally validated [10,12]. Generally, only a few comprehensive and accurate evaluation systems can adequately assess the prognosis of patients with SCAP admitted to the ICU at this stage.…”
Section: Introductionmentioning
confidence: 99%